plzzz ans me this question
Attachments:
![](https://hi-static.z-dn.net/files/d07/5ac040c867db67bf100b0863bc369f23.jpg)
Answers
Answered by
1
Given
a = 2x - 3 / 3 ; b = 7 - 3x / 4
a - b/ 5 = 1.....(1) (Given)
substitute a,b values in ..(1)
a - b / 5 = 1
cross multiply
a - b = 5
(2x - 3) / 3 - (7 - 3x) / 4 = 5
L.C.M of 4,3 = 4×3 = 12
(4(2x - 3) - 3(7 - 3x) ) / 12 = 5
cross multiply...
(4(2x - 3) - 3(7 - 3x) ) = 5×12
(4(2x - 3) - 3(7 - 3x) ) = 60
(4(2x) - 4(3)) -(3(7) -3(-3x)) = 60
we know that
[+ × - = -] [ - × - = +]
8x - 12 - 21 + 9x = 60
17x -33 = 60
17x = 60 + 33
17x = 93
x = 93/17...
a = 2x - 3 / 3 ; b = 7 - 3x / 4
a - b/ 5 = 1.....(1) (Given)
substitute a,b values in ..(1)
a - b / 5 = 1
cross multiply
a - b = 5
(2x - 3) / 3 - (7 - 3x) / 4 = 5
L.C.M of 4,3 = 4×3 = 12
(4(2x - 3) - 3(7 - 3x) ) / 12 = 5
cross multiply...
(4(2x - 3) - 3(7 - 3x) ) = 5×12
(4(2x - 3) - 3(7 - 3x) ) = 60
(4(2x) - 4(3)) -(3(7) -3(-3x)) = 60
we know that
[+ × - = -] [ - × - = +]
8x - 12 - 21 + 9x = 60
17x -33 = 60
17x = 60 + 33
17x = 93
x = 93/17...
Similar questions
CBSE BOARD XII,
8 months ago
Science,
8 months ago
History,
8 months ago
Biology,
1 year ago
Political Science,
1 year ago
Hindi,
1 year ago